92.9k views
3 votes
What is the answer ?

What is the answer ?-example-1
User Doggo
by
6.2k points

1 Answer

1 vote

Answer:

2y

Explanation:

Simplifying

21x + -42y = 0

Solving

21x + -42y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '42y' to each side of the equation.

21x + -42y + 42y = 0 + 42y

Combine like terms: -42y + 42y = 0

21x + 0 = 0 + 42y

21x = 0 + 42y

Remove the zero:

21x = 42y

Divide each side by '21'.

x = 2y

Simplifying

x = 2y

User Fintan Kearney
by
6.3k points